Healthcare and healthcare systems: inspiring progress and future prospects - Durrani, Hammad (mHealth, 2016)
Background: Healthcare systems globally have experienced intensive changes, reforms, developments, and improvement over the past 30 years. Multiple actors (governmental and non-governmental) and countries have played their part in the reformation of the global healthcare system. New opportunities are presenting themselves while multiple challenges still remain especially in developing countries. Better way to proceed would be to learn from historical patterns while we plan for the future in a technology-driven society with dynamic demographic, epidemiological and economic uncertainties. Methods: A structured review of both peer-reviewed and gray literature on the topic was carried out. Results: On the whole, people are healthier, doing better financially and live longer today than 30 years ago. The number of under-5 mortality worldwide has declined from 12.7 million in 1990 to 6.3 million in 2013. Infant and maternal mortality rates have also been reduced. However, both rates are still considered high in Africa and some Asian countries. The world’s population nearly doubled in these 30 years, from 4.8 billion in 1985 to 7.2 billion in 2015. The majority of the increasing population was coming from the least developed countries, i.e., 3.66 to 5.33 billion. The world will be short of 12.9 million health-care workers by 2035; today, that figure stands at 7.2 million. Health care expenditures among countries also show sharp differences. In high income countries, per person health expenditure is over USD 3,000 on average, while in poor countries, it is as low as USD 12, WHO estimate of minimum spending per person per year needed to provide basic, life-saving services is USD 44. The challenges faced by the global health system over the past 30 years have been increased in population and urbanization, behavioral changes, rise in chronic diseases, traumatic injuries, infectious diseases, specific regional conflicts and healthcare delivery security. Over the next 30 years, most of the world population growth will occur in the urban areas of poor countries. The rapid, unplanned and unsustainable style of urban development will make developing countries cities the key focal points for emerging environmental and health hazards. Changes will be seen in design, culture and practices of hospitals to better meet the needs of patients, families and providers. Top driving factors of global healthcare system for next 30 years will be leading causes of mortalities, non-health factors (impact of nutrition, sanitation and women’s empowerment), investment in health workforce and growth of medical tourism in future healthcare scenario. Conclusions: Evaluating the patterns of previous 30 years and predicting the progress and challenges of future health system are no rocket science. Medical care will be more self-directed in a more tech-savvy population as information will be more accessible and user friendly with higher quality. Health driving factors such as clean water, sanitation and food will take the center stage in humanities struggle and even increase population size.